2000
DOI: 10.1177/0273475300223003
|View full text |Cite
|
Sign up to set email alerts
|

When Were the Good Old Days? Revisiting Perceptions of Marketing Students’ Prior Preparation

Abstract: This study determines whether marketing professors’ perceptions of the preparedness of marketing majors have improved during the last decade. In 1985, Budden concluded that marketing professors perceived marketing majors as inadequately prepared to effectively pursue marketing curricula. This study reexamines those perceptions. The same questionnaire was administered to 600 marketing faculty members, and the results are very similar to the earlier study: communication and quantitative skills of marketing major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…In both cases, the marketing major attracts students with less interest and/ or aptitude in analysis. Attracting majors with stronger analytical capacity and interest is consistent with Aggarwal et al (2007) and Remington et al (2000).…”
supporting
confidence: 84%
“…In both cases, the marketing major attracts students with less interest and/ or aptitude in analysis. Attracting majors with stronger analytical capacity and interest is consistent with Aggarwal et al (2007) and Remington et al (2000).…”
supporting
confidence: 84%
“…According to job market statistics and survey results about marketing and business student's job search process, some of the abilities that are highly valued by today's employers have been in high demand for several years. Developing communication, presentation, and teamwork skills, for instance, is still encouraged by the faculty, preferred by employers of new hires over specific knowledge of the marketing function (Gaedeke, Tootelian, & Schaffer, 1983;Remington, Guidry, Budden, & Tanner, 2000;Taylor, 2003;), and acknowledged by students as important (Hite, Bellizzi, & McKinley, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Martin (1995) observed that faculty members may carry certain expectations of students, such as quantitative skill development, based on intuitive or personal experience that have no basis in educational research. Remington, Guidry, Budden, and Tanner (2000) and Galbraith and Haines (2000) offered a similar perspective, citing instances of "student negativity" that can result from poor student-faculty communication. To be effective, an outcomes assessment program must match stakeholders and their goals.…”
Section: Outcomes Assessmentmentioning
confidence: 99%